PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN DAN BIAYA AGENSI DENGAN TRANSPARANSI INFORMASI SEBAGAI VARIABEL PEMODERASI - Tarida, Theresa Dina; Prasetyo, Andrian Budi (Jurnal Analisis Bisnis Ekonomi, 2018)
This study aims to examine the effect of tax avoidance as an independent variable to firm value and agency cost as dependent variable and transparency of information as moderating variable. The population in this study is the manufacturing companies in Indonesia that are listed on Bursa Efek Indonesia in the year 2016. Samples used in this study are 89 companies that are selected using the  purpovise sampling method. This study used multiple liniear regression to examine the hypothesis. The result of this study shows that tax avoidance has a significant negative effect to the firm value. Tax avoidance also has significant positive effect to the agency cost. Lastly, transparency of information succeed to moderate the effect of tax avoidance on firm value become positive effect.